2008
DOI: 10.1111/j.1529-8817.2008.00520.x
|View full text |Cite
|
Sign up to set email alerts
|

ALGAE AS COMPETITORS FOR GLUCOSE WITH HETEROTROPHIC BACTERIA1

Abstract: Dissolved organic carbon (DOC) constitutes the bulk of organic carbon in aquatic environments. The importance of DOC utilization by mixotrophic algae is unclear since heterotrophic bacteria are regarded as more efficient users. We tested the hypothesis that algae decrease the DOC concentration in the light to lower levels than in darkness resulting in competitive exclusion of heterotrophic bacteria according to the mechanistic competition theory. We investigated (a) the uptake kinetics of glucose as a model su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 46 publications
1
28
0
1
Order By: Relevance
“…In the experiments presented here, no alga generated lower substrate levels in the light than in the dark, so that hypothesis (1) was not supported. This was also found in consumption experiments with glucose (Kamjunke et al, 2008). Furthermore, cyanobacteria and chlorophytes in our consumption experiments did not decrease substrate concentrations to lower levels than the heterotrophic bacteria.…”
Section: Discussionsupporting
confidence: 77%
“…In the experiments presented here, no alga generated lower substrate levels in the light than in the dark, so that hypothesis (1) was not supported. This was also found in consumption experiments with glucose (Kamjunke et al, 2008). Furthermore, cyanobacteria and chlorophytes in our consumption experiments did not decrease substrate concentrations to lower levels than the heterotrophic bacteria.…”
Section: Discussionsupporting
confidence: 77%
“…However, some studies have shown that several phytoplankton species do actively take up substrates at low concentrations so that they may, in fact, be competitive with bacteria [9], [10]. Among the organic substrates algae are able to use are pyruvate, acetate, lactate, ethanol, saturated fatty acids, glycolate, glycerol, hexoses, urea, and amino acids (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The molar C:P ratios of the medium were rather low (48 and 82) indicating a carbon limitation of bacteria, and also the higher bacterial biomass in the chemostats at 20°C compared to that at 15°C renders a phosphorus limitation unlikely. The equilibrium biomass of Chlorella in the chemostats was about 1,000-fold lower than in other experiments with glucose as carbon source and a plenty phosphorus supply (1,500 lg P l -1 ; Kamjunke et al, 2008) which was probably due to the lower phosphorus concentration. Furthermore, algal biomass was also much lower than bacterial biomass (about factor 50-100).…”
mentioning
confidence: 77%